2021
DOI: 10.18502/ijm.v13i6.8093
|View full text |Cite
|
Sign up to set email alerts
|

Partial purification, characterization and immobilization of a novel lipase from a native isolate of Lactobacillus fermentum

Abstract: Background and Objectives: Due to the widespread use of lipase enzymes in various industries, finding native lipase pro- ducing microorganisms is of great value and importance. In this study, screening of lipase-producing lactobacilli from native dairy products was performed. Materials and Methods: Qualitative evaluation of lipolytic activity of lipase-producing lactobacilli was performed in differ- ent media containing olive oil. A clear zone observation around the colonies indicated the lipolytic activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
1
1
0
Order By: Relevance
“…In the present study, the addition of fetal bovine serum was found to be more favorable for the increase in explant activity, which was confirmed by Alan et al who concluded that the addition of fetal bovine serum was beneficial in delaying the loss of explant activity (40). Furthermore, the results of the rumen explant activity assay showed that the optimal incubation time for rumen explants in dairy cows was 12 h, which is lower than the 24 h reported in other studies (38). This may be the result of differences between sheep and cow species, as sheep rumen epithelial cells can continuously and stably pass through generations.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…In the present study, the addition of fetal bovine serum was found to be more favorable for the increase in explant activity, which was confirmed by Alan et al who concluded that the addition of fetal bovine serum was beneficial in delaying the loss of explant activity (40). Furthermore, the results of the rumen explant activity assay showed that the optimal incubation time for rumen explants in dairy cows was 12 h, which is lower than the 24 h reported in other studies (38). This may be the result of differences between sheep and cow species, as sheep rumen epithelial cells can continuously and stably pass through generations.…”
Section: Discussionsupporting
confidence: 87%
“…Thus, this model was deemed suitable to address the objectives of the present study. Furthermore, the results of the rumen explant activity assay showed that the optimal incubation time for rumen explants in dairy cows was 12 h, which is lower than the 24 h reported in other studies (38). This may be the result of differences between sheep and cow species, as sheep rumen epithelial cells can continuously and stably pass through generations.…”
Section: Discussionmentioning
confidence: 67%